Soft forwarding technique for unitary space‐time modulation. Issue 16 (1st November 2013) - Liu, Qianqian; Cao, Yewen
Abstract : The authors propose two soft forwarding schemes for unitary space‐time modulation, namely estimate‐and‐forward (EF) and mutual information‐based forwarding (MIF), which are ideally suited for rapid piecewise‐constant fading scenarios with no channel state information both at transmitters and receivers. In the EF scheme, the relay regenerates signal via the conditional expectation of the source unitary space‐time (UST) signal given the received matrix at the relay node instead of hard decisions. The MIF scheme employs the instantaneous mutual information between the source UST signal and received matrix at the relay node as a measurement for maximum‐likelihood detection. The authors provide the relay forwarding functions, the normalisation factors, and the detection methods at the destination firstly. Above all, the generalised signal‐to‐noise ratio (SNR) at the destination for our unitary space‐time modulated relaying system is analysed and simulated firstly. Simulation results reveal that the proposed EF and MIF schemes can outperform the existing amplify‐and‐forward (AF) and detect‐and‐forward (DF) schemes in terms of bit‐error‐rate performances in most scenarios. For a parallel relay network with two relays, the proposed EF scheme achieves 2 and 3 dB SNR gain over AF and DF schemes, respectively. Moreover, the MIF scheme can further give about 1.5 dB SNR gain.